2014
DOI: 10.1097/rhu.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Anti-RNA Polymerase III Antibodies in the Diagnosis of Scleroderma Renal Crisis in the Absence of Skin Disease

Abstract: Scleroderma renal crisis (SRC) occurs in approximately 10% of patients with systemic sclerosis (SSc), particularly in those with diffuse skin disease. Scleroderma renal crisis has rarely been described to occur in patients with SSc without skin involvement. Scleroderma renal crisis without skin disease represents a major diagnostic challenge, particularly in patients without overt SSc involvement of other organ systems. It closely mimics the presentation of thrombotic thrombocytopenic purpura/ hemolytic uremic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…A higher prevalence of musculoskeletal involvement, gastric antral vascular ectasia, ILD, PAH, and scleroderma renal crisis (SRC) has been reported in ARA-positive patients ( 26 , 28 , 36 , 37 ). Notably, SRC was significantly more common in ARA-positive patients compared to ARA-negative ones ( P < 0.0001).…”
Section: Classical Disease-specific Autoantibodies In Clinical Manifementioning
confidence: 99%
“…A higher prevalence of musculoskeletal involvement, gastric antral vascular ectasia, ILD, PAH, and scleroderma renal crisis (SRC) has been reported in ARA-positive patients ( 26 , 28 , 36 , 37 ). Notably, SRC was significantly more common in ARA-positive patients compared to ARA-negative ones ( P < 0.0001).…”
Section: Classical Disease-specific Autoantibodies In Clinical Manifementioning
confidence: 99%
“…In line with previous reports, the RP3 cluster in our cohort was associated with dcSSc and higher risk for renal crisis. [67][68][69][70] In their study, Patterson et al found 2 different autoantibody clusters, depending on the intensity of R3 staining (cluster RNAP III strong and cluster RNAP III weak). 21 Since RP3 titers may change over time 68 , the authors concluded, that the clusters RNAP III strong and RNAP III weak may represent different temporal stages of SSc disease.…”
Section: Discussionmentioning
confidence: 94%
“…Skin sclerosis was absent at SRC onset, but the two patients eventually developed diffuse and rapidly progressive skin thickening. 66 Conversely, ILD that requires aggressive therapy and severe peripheral ulcers/gangrene rarely occurred in this subgroup. The prognosis of patients with anti-RNAP III Abs was the worst in all SSc patients until angiotensin-converting enzyme (ACE) inhibitors were developed.…”
Section: Ssc-specific Autoabsmentioning
confidence: 97%